Analisis Gelatin pada Soft Candy Produk Dalam Negeri Menggunakan Fourier Transform Infrared (FTIR) dengan Kombinasi Kemometrika - Salamah, Nina; Fatmawati, Arum; Guntarti, Any (Faculty of Pharmacy, Universitas Pancasila, 2023)
Gelatin is widely used in the food industry, including soft candy. It is generally sourced from cows and pigs. However, adding porcine gelatin to food will be problematic for the Muslim community due to its prohibition in their beliefs. Therefore, the soft candy’s components should be analysed to determine whether the functional groups are of bovine or porcine gelatin. From three local soft candy products in Indonesia, gelatin was isolated with acetone by vortexing and centrifugation. The supernatant was analysed with FTIR to determine its spectral profile. Furthermore, the wavenumbers and absorbances of gelatin’s functional groups were analysed in Minitab 18 with multivariate PLS and PCA. FTIR showed that gelatin contained proteins with O-H, aliphatic C-H, C=O, N-H, and C-N groups. PLS and PCA were conducted in the wavenumber range of 1576–1481 cm-1. The calibration yielded R2 = 0.9997 and RMSEC = 0.9376%. The internal validation showed R2 = 0.9998 and RMSECV = 1.29%, while the external validation produced R2 = 0.9996 and RMSEP = 1.04%. Clustering with PCA revealed that the gelatin sample from one soft candy was in the same quadrant as the reference bovine gelatin, while the other two were in different quadrants from both references.